(untitled) (Педагогіка вищої та середньої школи, 2010)
The article deals with the problem concerning the role of pedagogical condition in the evaluation of pupils’ cognitive activities. The system of education is Ю provide qualitively new level of general secondary, vocational and scientific training, all-round development of every person as a personality and the highest value in the society. According to the mentioned during the latest decades pedagogues have been improving forms and methods of training with the purpose of combining instructive, developing and educational objectives of the lesson. Significant place in didactics is taken among them by so-called non-traditional lessons.